ROY EBERHARDT’S ENVIRONMENTAL STEWARDSHIP IN CARL HIAASEN'S HOOT - Bahroen, Ichsan; Hartanto, Erika Citra Sari (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2022)
This study aims to describe the main character’s attitude to nature and it influences to his environmental stewardship in Carl Hiaasen’s novel Hoot. Deep Ecology theory by Bill Devall and George Sessions is applied in this study in studying the attitude of Roy Eberhardt to his environment and how it affects his environmental stewardship. This study used qualitative research as a method to analyze the data. The data of this study are Roy Eberhardt’s utterances, behavior, action and author’s narration in the novel. There are some conclusions based on the study; 1) Roy attitude’s toward nature are active and positive. It causes Roy to feel responsible to the preservation of environment around him like how he tries to save the owls. 2) Roy’s attitude that thought any creatures have the same right to life makes him to take non-violence action to save the nature. The attitude influences Roy to take peaceful actions to stop the owls’ nest destroyed by the industry.